Attitudes of Pregnant Women towards Husband's Attendance in Delivery Room in Erbil City - Mhadasa Farooq Saadi; Tiran Jamil Piro (Hawler Medical University, 2023)
Background and Objectives: Pregnancy is a beautiful and challenging time in a woman's life.   A pregnant woman needs more care and support from her husband and family during this time because of physical and hormonal changes in her body. Husbands' attendance and support of women during labor can positively affect pregnant women and child's health. The purpose of this study is to assess women's attitudes towards the presence of their husbands during labor in Erbil city.  Method: A descriptive cross-sectional study was conducted on pregnant women who visited primary health care and Maternity Teaching Hospital in Erbil city. Epi Info 7 was used to determine the sample size which Three hundred participants were the sample of the calculation. Statistical Package for Social Science (SPSS) version 26 was used to analyze and organize the data thorough using frequency, percentage, and chi-square test. Result: The study revealed that 62% of the participants were in the age group 20-30 years old. Most of the women obtained an elementary school certificate, with a percentage 23.3%. Most of the participants were urban residents, which was 81.3%. Regarding the income of the participants, the result indicated that most of them were in conditions sufficient for daily living, which was about 57.3%. Women expressed a good level of attitude towards husbands' attendance in the delivery room 80.3%. Conclusion: This survey illustrated that most pregnant women agreed to the husband's attendance in the delivery room. Pregnant women needed their husbands during labor which is important in their life.